Achieving Manufacturing Excellence through the Integration of Process Planning Change and Data-driven Simulation. (December 2020) - Wang, Xiaogang; Liu, Yiqun; He, Yang; Li, Nie; Mu, Hua; Bai, Yuewei
Abstract: In this paper, a data-driven simulation framework with the integration of process planning change is proposed. It solves the problems of insufficient throughput and unbalanced resource utilization caused by the extremely unbalanced working time, improper resources allocation. Integration with Flexsim using a 3D graphical user interface is designed to meet the needs of complex data management. Experiments were tested, and the results show that the proposed approach combines the real-time rescheduling and quickly changing.